Transverse-leaky-mode Characteristics of ARROW VCSELs - TEE, Chyng Wen (Institutional Knowledge at Singapore Management University, 2004)
Transverse-leaky-mode characteristics of antiresonant-reflecting-optical-waveguide (ARROW) vertical-cavity surface-emitting lasers (VCSELs) are studied. It is found that the suppression of high-order transverse leaky modes in ARROW VCSELs can be deteriorated by the influence of spatial hole burning and thermal lensing effects. On the other hand, a new design rule is proposed to deduce the optimum dimensions of ARROW so that the suppression of high-order transverse leaky modes can be enhanced. Furthermore, the turn-on transient response of ARROW VCSELs is investigated. It is found that the radiation loss has significant influence on the built-up time of the first-order transverse leaky mode.